2020
DOI: 10.3390/md18080418
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Renieramycins. Part 19: Semi-Syntheses of 22-O-Amino Ester and Hydroquinone 5-O-Amino Ester Derivatives of Renieramycin M and Their Cytotoxicity against Non-Small-Cell Lung Cancer Cell Lines

Abstract: Two new series of synthetic renieramycins including 22-O-amino ester and hydroquinone 5-O-amino ester derivatives of renieramycin M were semi-synthesized and evaluated for their cytotoxicity against the metastatic non-small-cell lung cancer H292 and H460 cell lines. Interestingly, the series of 22-O-amino ester derivatives displayed a potent cytotoxic activity greater than the hydroquinone derivatives. The most cytotoxic derivative of the series was the 22-O-(N-Boc-l-glycine) ester of renieramycin M (5a: IC50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…including renieramycin M and jorunnamycin A was highlighted through reports indicating suppression on anchorage-independent growth and sensitization of detachment-induced cell death in human lung cancer cells [31]. To maintain cytotoxicity and improve cancer selectivity, a semi-synthesized version of renieramycin M containing a hydroquinone amino ester extension was prepared to gain insights into anticancer activity and specific protein targets [34]. Taken together with the attenuation on migration and invasion activity presented in this study, the semi-synthesized hydroquinone monoester derivative of renieramycin M, 22-Boc-Gly-RM, has demonstrated multitargeted potential use against metastasis in human lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…including renieramycin M and jorunnamycin A was highlighted through reports indicating suppression on anchorage-independent growth and sensitization of detachment-induced cell death in human lung cancer cells [31]. To maintain cytotoxicity and improve cancer selectivity, a semi-synthesized version of renieramycin M containing a hydroquinone amino ester extension was prepared to gain insights into anticancer activity and specific protein targets [34]. Taken together with the attenuation on migration and invasion activity presented in this study, the semi-synthesized hydroquinone monoester derivative of renieramycin M, 22-Boc-Gly-RM, has demonstrated multitargeted potential use against metastasis in human lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…22-O-(N-Boc-l-glycine) ester of renieramycin M (22-Boc-Gly-RM) was semi-synthesized from jorunnamycin A by esterification as described in the previous studies [34,37] (see Online Resource 1). The obtained yellow powder of 22-Boc-Gly-RM was kept at room temperature away from light and moisture until use.…”
Section: Preparation Of 22-o-(n-boc-l-glycine) Ester Of Renieramycin Mmentioning
confidence: 99%
See 2 more Smart Citations
“…This natural marine product is similar to ecteinascidin 743 [ 30 ] and to renieramycin M, with the key difference being the side chain at the C-22 position ( Figure 1 ), as renieramycin M possesses an angeloyl ester while jorunnamycin A has an alcohol side chain instead. Jorunnamycin A and renieramycin M derivatives have exhibited potent cytotoxicity against human lung cancer cells [ 31 , 32 , 33 ]. A recent study revealed the inhibitory effect of renieramycin M on CSC features of lung cancer cells; however, its regulatory mechanism has never been investigated [ 34 ].…”
Section: Introductionmentioning
confidence: 99%